Tailoring fano resonance for flat-top broadband reflectors based on single guided-mode resonance - Heo, Hyungjun; Lee, Sangjun; Kim, Sangin (Journal of Lightwave Technology, 2019)
We investigated on the interaction between a single guided-mode resonance and Fabry-Perot resonance (FPR) in a high contrast grating (HCG) from a viewpoint of Fano resonance. It has been found that the background reflection due to the FPR in the HCG is useful to implement flat-top broadband reflectors via tailoring the phase polarity of Fano resonance. The novel conceptual approach was elucidated theoretically with the temporal coupled-mode theory (TCMT), which was confirmed by the Si HCG broadband reflector design of 380-nm bandwidth for R > 99.9 from 1400 to 1780 nm (a fractional bandwidth of 24.5%). The TCMT model was in good agreement with the rigorous coupled wave analysis calculation. We believe that our approach provides expanded understanding on Fano resonance in a grating, enabling more intuitive and simpler design of a flat-top broadband reflector with grating structures.
Keywords: Broadband reflector; Coupled mode theory; Fano resonances; Guided-mode resonance; High-contrast gratings; Broadband reflectors; Fano resonance; guided-mode resonance; high contrast gratings; temporal coupled mode theory